Industrial Training Report (FPA310) : Department of Agriculture of Sarawak, Jabatan Pertanian Bahagian Betong / Rahida Ahmad - Ahmad, Rahida (Universiti Teknologi MARA Cawangan Sarawak Kampus Mukah, 2019)
The Department of Agriculture of Sarawak was formed in 1924 when a British Director of Agriculture was appointed. This was the very beginning of Government's involvement developing agriculture in Sarawak. Agriculture development efforts specifically in crop have been implemented by the Department of Agriculture starting in 1929. Since then, it has grown rapidly in terms of manpower and coverage of programs and activities. Nowadays, the Department's focus is not only in crops, but also inland fisheries, research & development (K&D), farmers' institution development, veterinary and human resource development and extension.